2006
DOI: 10.1055/s-2006-925114
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Doses of Triiodothyronine Upregulate Lipogenic Enzyme Gene Expression in Rat White Adipose Tissue

Abstract: Triiodothyronine (T (3)) is known to increase liver lipogenic enzyme gene expression both in vivo and in tissue culture. Conflicting results have been reported on the effect of T (3) on lipogenic enzyme gene expression in white adipose tissue. The results presented in this paper indicate that administration of pharmacological doses of T (3) in rats leads to increased fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC), ATP-citrate lyase (ACL) and malic enzyme (ME) activity in white adipose tissue. The incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Glucose transport was differentially regulated with a significant upregulation of GLUT4 in WAT but not in other tissues. It supports well-known data on T3-related effects on FFA increase, an induction of hepatic, WAT, BAT and muscle-related gluconeogenesis and glycogenolysis [26,27,28,29,30,31,32,33]. This is further exemplified by data on the local availability of T3.…”
Section: Thyroid and Energy Regulation: Pathophysiological Consideratsupporting
confidence: 88%
“…Glucose transport was differentially regulated with a significant upregulation of GLUT4 in WAT but not in other tissues. It supports well-known data on T3-related effects on FFA increase, an induction of hepatic, WAT, BAT and muscle-related gluconeogenesis and glycogenolysis [26,27,28,29,30,31,32,33]. This is further exemplified by data on the local availability of T3.…”
Section: Thyroid and Energy Regulation: Pathophysiological Consideratsupporting
confidence: 88%
“…One experimental animal study reported that SREBP1c transcription was negatively regulated by TH via a putative negative thyroid hormone response element (nTRE) [36], but another study has shown that SREBP1c transcription is upregulated by non-genomic thyroid hormone signaling [37]. In our current study, the expressions of some hepatic TH-responsive proteins were sharply enhanced, such as SREBP1c, ACL [38], HMGCS1 [9], which are consistent with the promotions of fatty acid and cholesterol synthesis, respectively (Fig. 4A, 4B and 4D).…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, the same dose of T 3 up-regulated the expression of the malic enzyme gene (Figs. 4 and 5) and genes encoding other lipogenic enzymes (Zabrocka et al, 2006) in white adipose tissue. This suggests that the inhibitory effect of T 3 on leptin gene expression is rather specific but not a consequence of toxic action of the hormone on the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%